2008
DOI: 10.1345/aph.1l330
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction Between Everolimus and Antifungal Triazoles in a Liver Transplant Patient

Abstract: Our data suggest that during everolimus-azole cotreatment, a dose reduction of everolimus is needed to avoid overexposure. According to the different inhibitory potency of CYP3A4 activity, the reduction should be lower during fluconazole than during voriconazole cotreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…In some studies, a prompt reduction in the immunosuppressive drug dose was recommended to prevent overexposure and maintain therapeutic levels. 18,24,27 In a case report of a liver transplant patient, Pea et al 24 showed that a prompt reduction of the everolimus dosage from 0.75 mg twice daily to 0.25 mg/d allowed for therapeutic levels to be achieved. Similarly, Marty et al 18 noted in an allogenic hematopoietic stem cell transplantation that none of the patients with an empiric 90% sirolimus and 50% tacrolimus dosage reduction at the start of treatment with voriconazole had immunosuppressant levels above the therapeutic range during coadministration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, a prompt reduction in the immunosuppressive drug dose was recommended to prevent overexposure and maintain therapeutic levels. 18,24,27 In a case report of a liver transplant patient, Pea et al 24 showed that a prompt reduction of the everolimus dosage from 0.75 mg twice daily to 0.25 mg/d allowed for therapeutic levels to be achieved. Similarly, Marty et al 18 noted in an allogenic hematopoietic stem cell transplantation that none of the patients with an empiric 90% sirolimus and 50% tacrolimus dosage reduction at the start of treatment with voriconazole had immunosuppressant levels above the therapeutic range during coadministration.…”
Section: Discussionmentioning
confidence: 99%
“…18,24,27 Similarly, after the discontinuation of voriconazole, interaction also disappeared immediately, requiring an anticipated increase in the everolimus dose at the time of voriconazole withdrawal to avoid infratherapeutic levels. Nevertheless, some studies suggest that interaction takes much longer to disappear after azole discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Everolimus is distributed by P-glycoproteins and metabolized by CYP3A4 [44,45]. Although the pharmacokinetic profiles of stattic have not been clarified, there is no denying that the interactions between everolimus and stattic are due to pharmacokinetic actions.…”
Section: Discussionmentioning
confidence: 99%
“…The expected profile for PK DDI, with strong metabolism of the drug, has already been confirmed in the first case reports published. 73 TDM plays a crucial role in the monitoring of changes in ERL concentration. PK differences between ERL and SRL favor the adaptation of ERL doses during DDI management.…”
Section: Antiproliferative Effects and Cancersmentioning
confidence: 99%